Chronic Exposure of Renal Progenitor Cells (HRTPT) to As (III) Implicates Microfibril Associated Protein 5 (MFAP5) in the Activation of Carcinoembryonic Antigen Related Cell Adhesion Molecules (CEACAM 5 and 6) - Md Ehsanul Haque; Donald A. Sens; Scott H. Garrett (Current Issues in Molecular Biology)
Studies on populations exposed to inorganic arsenic (iAs) have shown an association with the development of chronic kidney disease (CKD) and renal cell carcinoma (RCC). However, there are few studies addressing how acute exposure of the human kidney to iAs might lead to the long-term alterations that might lead to CKD or RCC. This laboratory’s hypothesis is that renal exposure to iAs might alter the renal cells responsible for the repair and regeneration of nephrons damaged by iAs exposure or other renal toxicants. The kidney possesses a minority epithelial cell population that co-expresses PROM1 and CD24, which are believed to be involved in renal epithelial cell repair. The purpose of this work is to understand the pathogenesis of CKD in renal cortical epithelial cells. Our model consists of acute and chronic exposure of i-As (III) to “Human Renal Tubular Precursor TERT” (HRTPT). The microarray and gene validation study demonstrated a sudden induction of microfibril associated protein 5 (MFAP5) and carcinoembryonic antigen related cell adhesion molecule 5 and 6 (CEACAM 5 and 6) in chronic i-As (III)-exposed cells. Chronically exposed cells also exhibited an induction of the pAKT/AKT pathway and SOX9 transcription factor. The targeting of MFAP5 and CEACAM 5/6 could, therefore, provide a potential therapeutic approach to CKD.